Apportioned primary and secondary organic aerosol during pollution events of DISCOVER-AQ Houston. (1st January 2021) - Yoon, Subin; Ortiz, Stephanie M.; Clark, Adelaide E.; Barrett, Tate E.; Usenko, Sascha; Duvall, Rachelle M.; Ruiz, Lea Hildebrandt; Bean, Jeffrey K.; Faxon, Cameron B.; Flynn, James H.; Lefer, Barry L.; Leong, Yu Jun; et al.
Abstract: Understanding the drivers for high ozone (O3 ) and atmospheric particulate matter (PM) concentrations is a pressing issue in urban air quality, as this understanding informs decisions for control and mitigation of these key pollutants. The Houston, TX metropolitan area is an ideal location for studying the intersection between O3 and atmospheric secondary organic carbon (SOC) production due to the diversity of source types (urban, industrial, and biogenic) and the on- and off-shore cycling of air masses over Galveston Bay, TX. Detailed characterization of filter-based samples collected during Deriving Information on Surface Conditions from Column and VERtically Resolved Observations Relevant to Air Quality (DISCOVER-AQ) Houston field experiment in September 2013 were used to investigate sources and composition of organic carbon (OC) and potential relationships between daily maximum 8 h average O3 and PM. The current study employed a novel combination of chemical mass balance modeling defining primary (i.e. POC) versus secondary (i.e. SOC) organic carbon and radiocarbon ( 14 C) for apportionment of contemporary and fossil carbon. The apportioned sources include contemporary POC (biomass burning [BB], vegetative detritus), fossil POC (motor vehicle exhaust), biogenic SOC and fossil SOC. The filter-based results were then compared with real-time measurements by aerosol mass spectrometry. With these methods, a consistent urban background of contemporary carbon and motor vehicle exhaust was observed in the Houston metropolitan area. Real-time and filter-based characterization both showed that carbonaceous aerosols in Houston was highly impacted by SOC or oxidized OC, with much higher contributions from biogenic than fossil sources. However, fossil SOC concentration and fractional contribution had a stronger correlation with daily maximum 8 h average O3, peaking during high PM and O3 events. The results indicate that point source emissions processed by on- and off-shore wind cycles likely contribute to peak events for both PM and O3 in the greater Houston metropolitan area. Highlights: Contemporary carbon was largest contributor to total organic carbon in Houston. Secondary organic carbon contributed an average of 67% of total organic carbon. Secondary fossil carbon was variable ranging from 3 to 27% of total organic carbon. During peak ozone event, secondary fossil carbon was well correlated with ozone. Houston was impacted by sea breeze re-circulation during high pollutant day.